Ayub Khan : Pakistan's First Military Ruler - Altaf Gauhar (Lahore Sang-e-Meel Publications, 1994)
Ayub Khan: Pakistan's First Military Ruler, is a candid account of Ayub's rule. The much-publicized Decade of Reforms, the inner story of Ayub's election struggle against his chief contender, Miss Jinnah, and the story behind the Tashkent Declaration and the Agartala Conspiracy, are all under scrutiny. This analyses the 'two pleas' sent by Nehru to Kennedy and the resulting correspondence, and throws light on subjects that were previously unknown or shrouded in mystery.
Include Appendix and Index.
Keywords: Pakistan -- Politics and government -- Presidents